2023
DOI: 10.3390/jpm13020368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oblique Lumbar Interbody Fusion Combined with Posterior Decompression (OLIF-PD) and Posterior Lumbar Interbody Fusion (PLIF) in the Treatment of Adjacent Segmental Disease(ASD)

Abstract: Background: An unintended consequence following lumbar fusion is the development of adjacent segment disease (ASD). Oblique lumbar interbody fusion combined with posterior decompression (OLIF-PD) is another feasible option for ASD, and there is no literature report on this combined surgical strategy. Methods: A retrospective analysis was performed on 18 ASD patients requiring direct decompression in our hospital between September 2017 and January 2022. Among them, eight patients underwent OLIF-PD revision and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Several of those studies have also demonstrated the promising results of the application of OLIF in treating ASD [42][43][44]. Zhang et al compared the OLIF coupled with facet joint fusion with PLIF for revision of caudal adjacent segment disease after primary posterior lumbar fusion, and they concluded that OLIF is superior to PLIF in terms of reduced blood loss, shorter hospital stay, and lesser complications [42]. Zhu et al have compared stand-alone OLIF with PLIF in the revision of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Several of those studies have also demonstrated the promising results of the application of OLIF in treating ASD [42][43][44]. Zhang et al compared the OLIF coupled with facet joint fusion with PLIF for revision of caudal adjacent segment disease after primary posterior lumbar fusion, and they concluded that OLIF is superior to PLIF in terms of reduced blood loss, shorter hospital stay, and lesser complications [42]. Zhu et al have compared stand-alone OLIF with PLIF in the revision of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…The OLIF technique utilizes the natural corridor between the aorta and the psoas muscle, providing direct access to the intervertebral disc space while minimizing the risk of damage to the dural sac, nerve root, posterior muscle and bony structures, thereby reducing surgical trauma and associated complications [4,5]. Furthermore, the OLIF procedure obviates the need for intraoperative neuromonitoring and is relatively straightforward, rendering it a favored surgical approach in recent years [6].…”
Section: Introductionmentioning
confidence: 99%